2002
DOI: 10.1248/bpb.25.1179
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic and Anti-inflammatory Properties of the Ethanolic Extract from Gleditsia sinensis.

Abstract: In traditional Chinese medicine, various parts of Gleditsia sinensis LAM. (Leguminosae) are used for different remedies and express specific therapeutic values. The thorns of G. sinensis are used for the treatment of carbuncle, scabies and suppurative skin diseases, while the mature pods and anomalous fruits (fruits without seeds) are mainly used for treating apoplexy, headache, productive cough, asthma and scabies.1)The thorns of G. sinensis have been reported to show inhibitory effects on mast cell-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 10 publications
1
19
0
2
Order By: Relevance
“…Of these, various parts of Gleditsia sinensis have been evaluated in China and Korea for potential therapeutic effects (23). The fruits and seeds of Gleditsia sinensis have primarily been used for treating apoplexy, headache, asthma and scabies (24). On the other hand, the thorns are used for the treatment of carbuncle, scabies, suppurative skin diseases and anti-inflammatory effects (23).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, various parts of Gleditsia sinensis have been evaluated in China and Korea for potential therapeutic effects (23). The fruits and seeds of Gleditsia sinensis have primarily been used for treating apoplexy, headache, asthma and scabies (24). On the other hand, the thorns are used for the treatment of carbuncle, scabies, suppurative skin diseases and anti-inflammatory effects (23).…”
Section: Discussionmentioning
confidence: 99%
“…Para espécies deste gênero é comum o uso medicinal como registrado por Konoshima et al (1995), em fruto de G. japonica com atividade anti-HIV. Em frutos Gleditschia sinensis, foram descobertas atividades antileucêmicas (CHOW et al, 2003), inibição do crescimento de células tumorais (CHUI et al, 2004) e inibição de reações alérgicas e inflamatórias (DAI et al, 2002).…”
Section: Introductionunclassified
“…(Leguminosae) has been used in traditional oriental medicine to treat diverse diseases, such as suppuration, carbuncle, obesity, and thrombosis. [7][8][9][10] The crude extract of G. sinensis thorns has multiple pharmacological effects, including anti-mutagenic, anti-microbial, anti-allergic, anti-inflammatory, and anti-angiogenic effects. 11,12) Several previous studies reported anti-tumor effects of G. sinensis thorns in cancer cells and animal models, 7,13,14) but its active constituent is not clear.…”
mentioning
confidence: 99%